2017
DOI: 10.1088/1612-202x/aa6c1c
|View full text |Cite
|
Sign up to set email alerts
|

Elastic collision and breather formation of spatiotemporal vortex light bullets in a cubic-quintic nonlinear medium

Abstract: The statics and dynamics of a stable, mobile three-dimensional (3D) spatiotemporal vortex light bullet in a cubic-quintic nonlinear medium with a focusing cubic nonlinearity above a critical value and any defocusing quintic nonlinearity is considered. The present study is based on an analytic variational approximation and a full numerical solution of the 3D nonlinear Schrödinger equation.The 3D vortex bullet can propagate with a constant velocity. Stability of the vortex bullet is established numerically and v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…(93) below). Interactions between vortex solitons were investigated by means of direct simulations too [69,70]. Recent theoretical and experimental works with binary BEC have revealed a fascinating possibility of the creation of stable 3D and 2D soliton-shaped objects, which are stabilized by the LHY corrections to the mean-field (MF) theory, which account for the effect of quantum fluctuations around MF states [153].…”
Section: Interactions Between Multidimensional Solitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…(93) below). Interactions between vortex solitons were investigated by means of direct simulations too [69,70]. Recent theoretical and experimental works with binary BEC have revealed a fascinating possibility of the creation of stable 3D and 2D soliton-shaped objects, which are stabilized by the LHY corrections to the mean-field (MF) theory, which account for the effect of quantum fluctuations around MF states [153].…”
Section: Interactions Between Multidimensional Solitonsmentioning
confidence: 99%
“…( 93) below). Interactions between vortex solitons were investigated by means of direct simulations too [69,70].…”
Section: Interactions Between Multidimensional Solitonsmentioning
confidence: 99%
“…Apart from TG gas, quintic nonlinearity appears in a number of references. Recently, the formation of breathers through spatiotemporal vortex light bullets is discussed in a cubic-quintic nonlinear medium [37]. Oscillation of a dark soliton in a BEC with both cubic and quintic nonlinearities is observed, where the quintic nonlinearity in one dimension arises due to the interplay between the radial and axial degrees of freedom [38].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D quantum ball is stabilized in the presence of a repulsive three-body interaction and an adequate two-body attraction above a critical value [26][27][28] . It has been demonstrated that a tiny three-body repulsion stops the collapse and can stabilize a 3D quantum ball for zero 26 and non-zero angular momenta 29 . This gives the unique opportunity to study SSB in a 3D quantum ball bound solely by non-linear interactions placed in these parity-symmetric 1D potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical structure of the non-linear mean-field GP equation is the same as that of the NLS equation used to study pulse propagation in non-linear optics, although the physical meaning of the different terms is distinct in two cases. Hence, in a cubic-quintic non-linear medium [30][31][32] one can have a stable mobile 3D spatiotemporal light bullet 28,29 and a SSB can occur in that context also.…”
Section: Introductionmentioning
confidence: 99%